Assessing Strength of Pelvic Floor Muscle in Pelvic Organ Prolapse - Shrestha, Sabina; Shrestha, Madhu; Dangal, Ganesh; Shrestha, Alka (Birat Journal of Health Sciences, 2024)
Introduction: Pelvic organ prolapse (POP) is a debilitating condition affecting around 75% of women of different age group and parity. Reduced pelvic floor muscle strength in POP is associated with worse symptoms and prognosis. Objectives: To assess the pelvic floor muscle strength in pelvic organ prolapse of different stages Methodology: This cross sectional study included women with pelvic organ prolapse attending outpatient department of Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu. The clinical examination included the pelvic organ prolapse quantification (POP-Q)-system examination and Modified Oxford Scale. Statistical analysis included Pearson’s correlation (p<0.05). Results: Of the 145 women assessed; 12(8.3%) women had POP-Q stage 1 prolapse, 42 (29%) had stage 2, 77(53.1%) had stage 3 and 14 (9.7%) had stage 4.Mean ±SD Modified Oxford Scale was 3.26±1.2. There was significant association between POP and PFM strength (p-value 0.006). Conclusion: There is a significant association between POP and pelvic floor muscle strength.